A review: radar-based fall detection sensor / Hidayatusherlina Razali ... [et al.] - Razali, Hidayatusherlina; Abd. Rashid, Nur Emileen; Nasarudin, Muhammad Nazrin Farhan; Ismail, Nor Najwa; Ismail Khan, Zuhani; Enche Ab Rahim, Siti Amalina (UiTM Press, 2024)
Age-related physical changes make 60-year-olds more susceptible to injury and mortality. Fall detection sensors come in many varieties. However, the radar system is the most reliable detection method since it avoids the downsides of other sensors, such as discomfort, heavy computational processing, and privacy problems. Radar-based sensors can accurately capture Doppler frequency variations from human motion by utilising time-frequency representations and classification algorithms. Fall recognition involves steps: sensor type, data pre-processing, and data classification. This study examines radar's use in fall detection and how fall detection systems can enhance people's lives.